Using the Brainstorming Strategy to Develop Arabic Reading Comprehension for Seventh Grade Students in Jordan - Al-Hirsh, Sameer Mohammad Ali; Alslaiti, Feras Mahmoud (Dirasat: Human and Social Sciences, 2024)
Objectives: This study examines the effectiveness of using the brainstorming teaching strategy to develop critical and creative reading comprehension levels in the Arabic language subject for seventh grade students in Jordan. Methods: This study adopted the quasi-experimental approach. A survey question slip for Arabic language teachers, a brainstorming teaching plan, and a pre-posttest were designed in order to measure the levels of critical and creative reading skills. The sample of the study consists of 167 students selected randomly from 7045 seventh graders at schools under the first Directorate of Education in Irbid. The sample of the study was divided into one control group and one experimental group of female students, and one control group and one experimental group of male students. Results: The study showed that there were statistically significant differences between the means of scores of the selected sample concerning their performance in both the critical and creative reading posttests, which can be attributed to the brainstorming strategy and in favor of the experimental group. The study also showed that there were no statistically significant differences between the means of scores of the selected sample in terms of their performance in the critical reading posttest that can be attributed to gender. In addition, the study showed that there were statistically significant differences between the means of scores of the selected sample regarding their performance in the creative reading posttest which can be attributed to gender and in favor of female students. Conclusions: Brainstorming improves students’ both critical and creative reading skills in Arabic. The study recommends that Arabic language teachers apply the brainstorming strategy to teaching different Arabic textbooks and for other grades, focusing on adolescents.